Study of technological indicators of two-layer knitted fabrics obtained on long Xing LXA 252 knitting machine - Sheraliyeva, Risolat; O'ralov, Lazizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, in order to expand the assortment of two-layer knitted fabrics, save raw material consumption, and determine their technological parameters, 3 samples were woven and their technological parameters were analyzed and recommended for production.